Cabozantinib and Panitumumab for RAS Wild‐Type Metastatic Colorectal Cancer. (9th February 2021) - Strickler, John H.; Rushing, Christel N.; Uronis, Hope E.; Morse, Michael A.; Niedzwiecki, Donna; Blobe, Gerard C.; Moyer, Ashley N.; Bolch, Emily; Webb, Renee; Haley, Sherri; Hatch, Ace J.; Altomare, Ivy P.; et al.
Abstract: Lessons Learned: Antitumor activity was observed in the study population. Dose modifications of cabozantinib improve long‐term tolerability. Biomarkers are needed to identify patient populations most likely to benefit. Further study of cabozantinib with or without panitumumab in patients with metastatic colorectal cancer is warranted. Background: The epidermal growth factor receptor (EGFR) antibody panitumumab is active in patients with RAS wild‐type (WT) metastatic colorectal cancer (mCRC), but nearly all patients experience resistance. MET amplification is a driver of panitumumab resistance. Cabozantinib is an inhibitor of multiple kinases, including vascular endothelial growth factor receptor 2 (VEGFR2) and c‐MET, and may delay or reverse anti‐EGFR resistance. Methods: In this phase Ib clinical trial, we established the maximum tolerated dose (MTD) and recommended phase II dose (RP2D) of cabozantinib and panitumumab. We then treated an expansion cohort to further describe the tolerability and clinical activity of the RP2D. Eligibility included patients with KRAS WT mCRC (later amended to include only RAS WT mCRC) who had received prior treatment with a fluoropyrimidine, oxaliplatin, irinotecan, and bevacizumab. Results: Twenty‐five patients were enrolled and treated. The MTD/RP2D was cabozantinib 60 mg p.o. daily and panitumumab 6 mg/kg I.V. every 2 weeks. The objective response rate (ORR) was 16%. Median progression free survival (PFS) was 3.7 months (90% confidence interval [CI], 2.3–7.1). Median overall survival (OS) was 12.1 months (90% CI, 7.5–14.3). Five patients (20%) discontinued treatment due to toxicity, and 18 patients (72%) required a dose reduction of cabozantinib. Conclusion: The combination of cabozantinib and panitumumab has activity. Dose reductions of cabozantinib improve tolerability.